Plastic marine pollution - Vanrykel, Anouck (Acta hydrotechnica, 2017)
A large amount of plastic products end up in the oceans as plastic waste. Plastic parts break down into a considerable amount of microplastics that affect marine biota. The effect of plastic particles on marine biota is analyzed and a short overview of the amount and dimensions of plastic particles in the world%s oceans are given herein. This paper deals with the connection between waste streams and the calculated distribution of plastic concentration in the oceans. Using an oceanographic model of floating debris dispersal this was estimated at a minimum of 5.25 trillion plastic particles in the world%s oceans, weighing a total of 268,940 tons. After quantifying the plastic debris, a comparison is made among the world%s oceans. Discrepancies from the expected results are identified and explained. Finally, some ideas and solutions are given for reducing the amount of plastic litter in the oceans.
Keywords: marine biota; measurements; meritve; microplastics; mikroplastika; morska biota; ocean; onesnaženje; pollution